2011
DOI: 10.1080/08923647.2011.618314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer-Led Online Asynchronous Discussion on Undergraduate Students' Cognitive Achievement

Abstract: This study investigated the effect of peer leadership on students' cognitive achievement in online asynchronous discussions. Undergraduate students from a large online course were randomly assigned into groups for four asynchronous discussions, with each group having two to three peer leaders. Results of the mixed-method analysis revealed that the quality of student leaders' lower-order cognitive achievement in online discussion was significantly better than that of student responders. Student leaders' higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 28 publications
4
16
1
Order By: Relevance
“…Our results indicate that student participation improved during the course only when the social tutor was present (question 1). This finding is in agreement with what previous studies show regarding the positive effects of peer moderation on students’ participation in online discussions (eg, Xie, Yu, & Bradshaw, ; Zha & Ottendorfer, ). However, it should be noted that in those previous studies, the peer moderator was introduced to lead the online discussions.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that student participation improved during the course only when the social tutor was present (question 1). This finding is in agreement with what previous studies show regarding the positive effects of peer moderation on students’ participation in online discussions (eg, Xie, Yu, & Bradshaw, ; Zha & Ottendorfer, ). However, it should be noted that in those previous studies, the peer moderator was introduced to lead the online discussions.…”
Section: Discussionsupporting
confidence: 93%
“…Four roles (knowledge constructors, team builders, motivators and organisers) coupled with sixteen strategies emerged from the data. Consistent with previous studies (De Backer, Van Keer, & Valcke, 2012;Ghadirian & Ayub, 2017;Hew, 2015;Snyder & Dringus, 2014;Xie et al, 2014;Zha & Ottendorfer, 2011), this study lent further evidence to the argument that student-led online discussions can be a viable and effective alternative even for L2 learners. The allocation of facilitating roles can empower learners, particularly those learners who lack the confidence and/or skills to lead.…”
Section: Conclusion Pedagogical Implications and Limitationssupporting
confidence: 90%
“…Furthermore, peer facilitation has been found to be positively correlated with students' higher-order cognition. Framing their study through the lens of Bloom's taxonomy of learning domains, Zha and Ottendorfer (2011) focused on the effect of peer moderation on assigned student moderators' cognitive achievement. The results revealed that lower-order cognitions were achieved in all students while peer moderators outperformed their peers in higher-order thinking.…”
Section: Research Into Peer-moderated Asynchronous Online Discussionmentioning
confidence: 99%
“…Student-led discussion enhances student involvement and satisfaction while enabling better career preparation, use of time, and achievement of goals (Dröge & Spreng, 1996). Student leaders have a higher level of achievement when they are given the responsibility of leading (Zha & Ottendorfer, 2011).…”
Section: Student-led Discussionmentioning
confidence: 99%
“…Research shows that how effectively student leaders facilitate discussion affects other students' participation (Zha & Ottendorfer, 2011). It is important that all students are given the chance to lead over the course of the class (Zha & Ottendorfer, 2011).…”
Section: Student-led Discussionmentioning
confidence: 99%